The relevance of education today - Živoder, Andreja (Teorija in praksa, 2011)
The article interprets the results of qualitative research within the GOETE project. It discusses how 9th grade students relate to the relevance of education today by analysing their educational decisions within the framework of the ideology of choice in contemporary Slovenian society. It attempts to categorise reasons for the relevance of education and provide two typical strategies students employ in order to be able to make educational choices in a socio-economic environment which does not favour such important life-educational decisions.
Keywords: School children; Učenci; Izobraževanje; Education; Izbira; Choice; Decision making; Odločanje; Slovenia; Slovenija; raziskave